Abortion Legalization and Child in The Womb Right to Life: A Study from Indonesia - Wiryani, Fifik; Andang, Widjanarko; Nasser, M. (International Journal of Criminology and Sociology, 2022)
Based on the Indonesian legal system, women’s reproductive and unborn child’s rights to life are equally important. A woman has the right to determine her pregnancy period or even reject her unwanted pregnancy. On one side, legal abortion is part of women’s reproductive rights. On the other side, the unborn child’s life in the womb is also protected by law. Any attempt to harm the fetus’ well-being or deliberately dispose of its life is illegal. Generally, Indonesian are against abortion. However, in specific cases, abortion legalization occurs when the pregnancy becomes harmful and endangering the mother’s life. In fact, in certain labor cases, the doctor must do an abortion to save the mother’s life. Through Health Act No. 36 of 2009 Article 75, abortion is permitted with emergencies on mothers and rape victims. This paper aims to analyze whether two indications of abortion legalization written on the Health Act are still acceptable from the standpoint of unborn child rights. As normative research, this paper uses both statutory and medical approaches.